Ethical Competence and Possibilities of Dialogic Education - Kincāns, Vladimirs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article is dedicated to the possibilities of shaping ethical competence through dialogic education. The problem of shaping a future specialist’s ethical competence in many respects depends on the quality of teaching ethics as a training discipline as well as on the teaching methods. Dialogic education is the most promising form of moral values introduction and ethical competence development.